Recurrent Guillian Barre’ Syndrome vs acute onset CIDP - study of 2 cases. - Mohan, Sankalp; Dhamne, Megha Chetan (RRNMF Neuromuscular Journal, 2024)
The most common acquired immune mediated polyneuropathies are acute inflammatory demyelinating polyradiculoneuropathy(AIDP), a form of Gullian Barre syndrome (GBS) and chronic inflammatory demyelinating polyradiculoneuropathy(CIDP). Sixteen percent of CIDP patients may present acutely like AIDP, developing in less than 8 weeks. Also GBS which is usually monophasic can have recurrences . Distinguishing Acute onset CIDP(A-CIDP) and recurrent AIDP may be difficult in early stages but may be crucial to guide the treatment strategies.